1999
DOI: 10.1016/s0741-5214(99)70312-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ocular perfusion after carotid endarterectomy with color-flow duplex scanning

Abstract: Severe carotid stenosis may be associated with reduced ocular perfusion, which can be quantitatively evaluated with ODS. Reduced OA and CRA flow velocities are corrected with successful CEA. The patients with ocular symptoms were observed to have significant reductions in CRA flow velocities. Reversed flow in the OA was not a marker for ocular symptoms in this study. ODS can identify global ocular ischemia and may be helpful in the evaluation of patients with atypical visual symptoms or with amaurosis fugax an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 24 publications
3
14
1
2
Order By: Relevance
“…In addition, an anastomosis of the external carotid circulation to the ICA (for example, the orbital branch of the middle meningeal artery to the ophthalmic artery) may form with a carotid stenosis [6]. Approximately 28-35% of preoperative CEA patients exhibit reversed flow in the ophthalmic artery before surgery [7][8][9]. Transient blindness and amaurosis fugax have been reported in patients with a totally occluded ipsilateral ICA, clearly establishing the collateral pathway as a mechanism for retinal embolization [10].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an anastomosis of the external carotid circulation to the ICA (for example, the orbital branch of the middle meningeal artery to the ophthalmic artery) may form with a carotid stenosis [6]. Approximately 28-35% of preoperative CEA patients exhibit reversed flow in the ophthalmic artery before surgery [7][8][9]. Transient blindness and amaurosis fugax have been reported in patients with a totally occluded ipsilateral ICA, clearly establishing the collateral pathway as a mechanism for retinal embolization [10].…”
Section: Discussionmentioning
confidence: 99%
“…The OA is located downstream of the ICA, and the inflow artery for the OA is the ICA. Severe CS was associated with a marked reduction in OA and CRA flow velocities, which were corrected with successful CEA [15]. Kawaguchi et al demonstrated that the BFV in OA increased from 9 ± 5 cm/s to 21 ± 5 cm/s one week after CEA [16].…”
Section: Discussionmentioning
confidence: 99%
“…Rutgers et al indicated that the proportion of reversed OA flow ipsilateral to severe CS decreased significantly from 42% before to 5% at six months after CEA [12]. Cohn Jr. et al reported that eight patients with preoperative OA flow reversal had a return of normal OA flow within one month following CEA [15]. Zbornikova and Skoglund demonstrated that a change in the flow direction from being retrograde to antegrade was noted in 9/10 patients (90%) within forty-eight hours after CEA [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High diastolic systemic arterial pressures may be protective, maintaining OPP throughout the cardiac cycle despite peri-operative elevations in IOP. Conversely, carotid artery stenosis is associated with reduced ipsilateral OPP 6 and may risk TRAO in the context of relatively minor fluctuations in IOP.…”
mentioning
confidence: 99%